Tissue Specific Expression Levels of Apoptosis Involved Genes Have Correlations with Codon and Amino Acid Usage - Mohammadreza Hajjari; Iman Sadeghi; Abbas Salavaty; Habib Nasiri; Maryam Tahmasebi Birgani (Genomics & Informatics)
Different mechanisms, including transcriptional and post transcriptional processes, regulate tissue specific expression of genes. In this study, we report differences in gene/protein compositional features between apoptosis involved genes selectively expressed in human tissues. We found some correlations between codon/amino acid usage and tissue specific expression level of genes. The findings can be significant for understanding the translational selection on these features. The selection may play an important role in the differentiation of human tissues and can be considered for future studies in diagnosis of some diseases such as cancer.